2016
DOI: 10.1111/1756-185x.12947
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis in childhood human immunodeficiency virus infection predominantly associated with human leukocyte antigen B27

Abstract: Aim: Children with human immunodeficiency virus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…There are only a few studies worldwide on musculoskeletal manifestations involving pediatric population with HIV (10–14). One recent single-center case series from northern India has reported four children with HIV infection who developed arthritis (32). So, the index study is the first large-scale prospective study of its kind to address the spectrum of rheumatological manifestations in children infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies worldwide on musculoskeletal manifestations involving pediatric population with HIV (10–14). One recent single-center case series from northern India has reported four children with HIV infection who developed arthritis (32). So, the index study is the first large-scale prospective study of its kind to address the spectrum of rheumatological manifestations in children infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of musculoskeletal manifestations in HIV-infected children in India reported 3 cases of inflammatory arthritis, all of which occurred in older girls with advanced immunosuppression ( 60 ). Another report from India described a single case of HIV arthropathy, and three cases of HLA-B27-associated arthritis in HIV-infected children ( 61 ). A study of juvenile idiopathic arthritis from Zambia reported 7 cases of arthritis in HIV-infected children, but did not provide details of subgroup analysis ( 62 ).…”
Section: Introductionmentioning
confidence: 99%